PERANAN PEMERINTAHAN TERHADAP IMPLEMENTASI PENANGGULANGAN DAN PENCEGAHAN NARKOBA DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Andi Muhammad Arifin Nu'mang (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
The purpose of this study is to determine the Role of Regional Government Towards the Implementation of Regional Regulation No. 2 of 2014 Regarding Drug Prevention and Prevention in the District of Maritengngae Sidenreng Rappang Regency and to determine the factors of the Role of Regional Government Towards the Implementation of Regional Regulation No. 2 of 2014 Regarding Drug Prevention and Prevention In the District of Maritengngae, Sidenreng Rappang Regency.The population in this study was the whole of the maritengae sub-district community, amounting to 49,556 souls. The sampling technique uses the Slovin formula with a result of 100, taken based on the Probability sampling technique, more precisely Random sampling. This type of research is quantitative descriptive. Data collection techniques used in this study were observation, questionnaires, and documentation.Based on the results of the questionnaire on the Role of Regional Government Towards the Implementation of Regional Regulation No. 2 of 2014 concerning Drug Prevention and Prevention in the District of Maritengngae, Sidenreng Rappang Regency. The role of the regional government obtained an average percentage of 47.68% included in the category of "Good Enough". Implementation of regional regulations averaged a percentage of 39.7% and was in the "Poor" category. Internal factors that influence the role of local governments are on average a percentage of 31% and are in the "Poor" category. External factors have an average percentage of 50.6% and are in the "Good Enough" category.